A Study On The Contrasting Theories Of Investment Behaviour - Samuel, Ms. Shwetha S; Tantia, Dr. Veerta (Migration Letters, 2024)
The primary tenet of standard finance is that investors are logical and weigh all available information when making portfolio investment decisions. This is supported by the Efficient Market Hypothesis, a key theory of standard finance. Psychologists have questioned this premise over time, claiming that investors are not rational beings since cognitive and psychological flaws affect their decisions. Behavioural finance is a new area of financial economics that emerged as a result of the efforts made in this direction by some well-known psychologists. The study of behavioural finance takes into account how different psychological characteristics influence the choices that investors make. In light of this, the current research presents a thorough and unique analysis of hypotheses pertaining to investment behaviour, both in support of and opposition to long-held beliefs. Based on the literature study, it can be inferred that the goal of behavioural finance is to close the gap between predicted and actual behaviour. It is impossible to view behavioural finance as a distinct field; rather, it is a component of conventional finance. Compared to the Efficient Market Hypothesis, the adaptive market hypothesis provides a more thorough explanation of market behaviour.